FATIGUE LIFE OF WELDED ROADHEADER DRIVE DEPARTMENT UNDER DIFFERENT CROSS SECTIONAL - MAO Jun; YANG XinWei; CHEN HongYue (Jixie qiangdu)
According to the effect of welding residual stress on fatigue fracture in crawler frame drive department when roadheader cross sectional,mechanical model of roadheader cross sectional was established,using MATLAB language calculate the different cross sectional angles of lateral force on the crawler frame;distribution law of welding residual stress of crawler frame drive department was analyzed by using finite element method.Based on the above analysis,and equivalent stresses under different cross-sectional angles on driver fatigue life analysis.The results show that the minimum lateral loads on the crawler frame and drive department weld fatigue life the greatest when the cross sectional angles of 5°.